2021
DOI: 10.3389/fnins.2021.594448
|View full text |Cite
|
Sign up to set email alerts
|

Adult Hippocampal Neurogenesis and Affective Disorders: New Neurons for Psychic Well-Being

Abstract: A paradigm shift in neuroscience was the discovery that new neurons are constantly produced in the adult mammalian brain of several species, including Homo sapiens. These new-born cells are formed in some main neurogenic niches, including the subventricular zone (SVZ) at the margin of the lateral ventricle and subgranular zone (SGZ) in the hippocampal dentate gyrus (DG). In the DG, neuroblasts derive from SGZ progenitors and migrate to the hippocampal granular layer becoming adult granule cells, which are inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 115 publications
1
22
0
2
Order By: Relevance
“…Moreover, a recent study showed that decreasing Arg1 + microglia in the hippocampus by knocking down the microglial IL4R suppressed hippocampal neurogenesis and enhanced vulnerability to CUMS, whereas increasing Arg1 + microglia in the hippocampus by enhancing IL4 signaling restored hippocampal neurogenesis and the resilience to stress-induced depression via brain-derived neurotropic factor (BDNF) ( Zhang et al, 2021 ). Activated microglia along with impaired adult hippocampal neurogenesis during chronic stress may hence jointly contribute to the pathophysiology underlying stress susceptibility in psychiatric disorders ( Madore et al, 2020 ; Gomes-Leal, 2021 ). Whether microglial regulation of adult hippocampal neurogenesis in stress susceptibility or resilience is sex-dependent warrants future research.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study showed that decreasing Arg1 + microglia in the hippocampus by knocking down the microglial IL4R suppressed hippocampal neurogenesis and enhanced vulnerability to CUMS, whereas increasing Arg1 + microglia in the hippocampus by enhancing IL4 signaling restored hippocampal neurogenesis and the resilience to stress-induced depression via brain-derived neurotropic factor (BDNF) ( Zhang et al, 2021 ). Activated microglia along with impaired adult hippocampal neurogenesis during chronic stress may hence jointly contribute to the pathophysiology underlying stress susceptibility in psychiatric disorders ( Madore et al, 2020 ; Gomes-Leal, 2021 ). Whether microglial regulation of adult hippocampal neurogenesis in stress susceptibility or resilience is sex-dependent warrants future research.…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampal neurogenesis is associated with the inherent depression pathophysiology as well as the response to antidepressants [ 91 , 92 ]. Hippocampal neurogenesis defects are related to depression-related symptoms, such as hopelessness and helplessness [ 13 , 14 , 93 , 94 ]. Research indicates that defective neurogenesis alters a spectrum of physiological processes, including inflammation [ 95 , 96 ], the hypothalamic–pituitary–adrenal axis [ 97 ], and neurotrophic factors [ 98 , 99 ], which are all crucial to depression or stress responses.…”
Section: Entorhinal Cortex-regulated Hippocampal Neurogenesis For Emotional Regulationmentioning
confidence: 99%
“…Pioneering preclinical studies examining entorhinal cortex-regulated hippocampal neurogenesis and cognitive and emotional symptoms of depression have led to initial advances in the neural circuitry–neurogenesis model of depression. Gomes-Leal et al [ 13 ] suggested activation of reward centers for psychic well-being, for which good feelings are mediated in reward centers, such as nucleus accumbens and tegmental ventral area. Nevertheless, the mechanism of the depression model should be further elucidated in two parallel directions.…”
Section: Suggestions For the Neural Circuitry-neurogenesis Model Of Depressionmentioning
confidence: 99%
See 2 more Smart Citations